Empathic Narrative of Online Political Communication - Wang, Yuqi; Lu, Lihong; Zhou, Zhibo; Zhu, Jing (Frontiers in Psychology, 2022)
With the rapid development of the Internet, political culture plays an increasingly prominent role in ethical guidance and value orientation, and the intergenerational inheritance of political culture in various countries needs to be carried out in a sophisticated way. From the perspective of empathic narrative, this study applies the network text analysis method to detect the cultural communication regularities to the contemporary young adults in online political communication and explores contemporary young adults' perception of online political culture through empirical analysis. Moreover, it proposes the empathic narrative logic of online political communication by comparing the existing communication elements and the urgently needed communication elements. Our findings suggest that we need to deepen the cognitive empathy, stabilize the emotional empathy, and adjust the emotional bias in online political communication.